If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + 2 = 2x + 2 + -1(x + 6) Reorder the terms: -2 + 2 + 3x = 2x + 2 + -1(x + 6) Combine like terms: -2 + 2 = 0 0 + 3x = 2x + 2 + -1(x + 6) 3x = 2x + 2 + -1(x + 6) Reorder the terms: 3x = 2x + 2 + -1(6 + x) 3x = 2x + 2 + (6 * -1 + x * -1) 3x = 2x + 2 + (-6 + -1x) Reorder the terms: 3x = 2 + -6 + 2x + -1x Combine like terms: 2 + -6 = -4 3x = -4 + 2x + -1x Combine like terms: 2x + -1x = 1x 3x = -4 + 1x Solving 3x = -4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3x + -1x = -4 + 1x + -1x Combine like terms: 3x + -1x = 2x 2x = -4 + 1x + -1x Combine like terms: 1x + -1x = 0 2x = -4 + 0 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 125+10h=230+7 | | 40t=60t(t-1) | | 7(3a-1)=91 | | 1.99d=20+.49d | | -4=-8+2w | | 5+5+4x+48=90 | | (-4,2),y=-1/2x-6 | | 3-(2/9)b=(1/3)b-7 | | 3/7w= | | 4x^2-9y^2-8x+40=0 | | 14x+3y=148 | | -7x+5=4x-94 | | -2/3y-4=1 | | 5+.5x+3=-7 | | =-9x^2+7x+4 | | 7x=4x-4-5 | | 70+4.50= | | 2x+(4c-3x)-8c= | | 4/5b-9=3 | | 7/2A-2/3A | | 4x-9(0)=2 | | =-8x^2+3x+9 | | (1/3)e^-4t=0.1 | | x^2-1000x+7.936=0 | | -16t^2+486=0 | | 6w+-5+8w-2w-3=9w-24 | | 4.5+70= | | x+2=6x-48 | | -3(w+4)=-8 | | 6/t=2/7 | | =-3x^2+9x+7 | | -3y=-2x-9 |